Combining Ability and Gene Action Estimates of Eight Parent Diallel Crosses of Chickpea for Ascochyta Blight - Mohamed Labdi; Samia Ghomari; Samia Hamdi (Advances in Agriculture)
Ascochyta blight resistance was studied in half-diallel cross involving eight genotypes of chickpea at seedling and adult stages. The disease was rated in the greenhouse with a modified scale from 0 to 100%. The diallel analysis was performed on 28 F1 and their F2. The results were analyzed with the Hayman and Griffing methods. The general combining ability is most important for two generations, is highly significant for the two stages, and is more important than specific combining ability. This result reflects a strong preponderance of additive effects and epistasis additive × additive with respect to dominance effects in this material for the two generations, which shows the predominance of additive versus dominance. Estimates of heritability are very high. The additive effects have the highest value indicating the importance of this component for resistance to Ascochyta. For seedling stage, the negative sign of F for both generations indicates that there are much more recessive alleles that affect resistance to the disease. In adult stage, F is positive in both generations and shows more dominant alleles that control plant reaction to pathogen. H2 is positive in both generations which show that dominant genes are acting mostly towards the susceptibility.